Sorbitane Monostearate and Cholesterol based Niosomes for Oral Delivery of Telmisartan - Ahad, Abdul; Raish, Mohammad; Al-Jenoobi, Fahad I.; Al-Mohizea, Abdullah M. (Current Drug Delivery, 2018)
Background: Niosomes are non-ionic surfactant vesicles used as drug carriers for encapsulating both hydrophobic and hydrophilic drugs. The aim of the present study was to prepare and characterize niosomes formulations for oral delivery of telmisartan and evaluated for its antihypertensive activity. Method: Telmisartan loaded niosomes were prepared using thin film hydration method by varying the Span 60 and cholesterol at several molar ratios and characterized for vesicles size, polydispersity index, zeta potential, entrapment efficiency. The in vivo antihypertensive study of optimized formulation and molecular impact of angiotensin II type-1 receptor (AT1R) messenger Ribonucleic acid (mRNA) and protein expression on smooth vascular muscles of aorta was determined by real-time polymerase chain reaction (RT-PCR) and western blot analysis in Wistar albino rats. Results: The optimized niosomes formulation NS6 presented vesicles size of 618.47 nm, polydispersity index of 0.86, with entrapment efficiency of 83.83% and possesses negative charge. In vivo study showed that the optimized formulation could reduce the systolic blood pressure in methyl prednisolone acetate induced hypertensive rats in close proximity to normal range of systolic blood pressure and maintain it over an extended period. In addition, telmisartan loaded niosomes treatment to hypertensive rats significantly attenuates the raised mRNA level and protein level of AT1R gene in comparison to hypertensive rats. Conclusion: Results of present study confer the potential of developed niosomes as suitable carriers for improved oral delivery of telmisartan.
Keywords: Antihypertensive